Evidence‐based occupational therapy for people with dementia and their families: What clinical practice guidelines tell us and implications for practice. (3rd October 2016) - Laver, Kate; Cumming, Robert; Dyer, Suzanne; Agar, Meera; Anstey, Kaarin J; Beattie, Elizabeth; Brodaty, Henry; Broe, Tony; Clemson, Lindy; Crotty, Maria; Dietz, Margaret; Draper, Brian; et al.
Abstract: Background/aim: The first evidence‐based Clinical Practice Guidelines and Principles of Care for People with Dementia in Australia have been released. The Guidelines detail a number of important evidence‐based recommendations for occupational therapists. The aim of this paper is (1) to provide an overview of Guideline development, and (2) to describe the evidence supporting a recommendation for occupational therapy. Common characteristics of effective occupational therapy programmes for people with dementia are described. Methods: Guideline development involved adaptation of existing high‐quality guidelines developed overseas and 17 systematic reviews to ensure that the most recent high‐quality evidence was included. One of the systematic reviews involved examining the evidence for interventions to promote independence in people with dementia. Specifically, we looked at the evidence for occupational therapy and its effect on activities of daily living, quality of life and carer impact. Results: A total of 109 recommendations are included in the Guidelines. Occupational therapy was found to significantly increase independence in activities of daily living and improve quality of life. Effective occupational therapy programmes involve: environmental assessment, problem solving strategies, carer education and interactive carer skills training. Conclusion: Occupational therapists working with people with dementia in community settings should ensure that their time is spent on those aspects of intervention that are shown to be effective.